On the global asymptotic stability of solutions to a generalised Lengyel–Epstein system. (June 2017) - Abdelmalek, Salem; Bendoukha, Samir
Abstract: This paper presents a Lengyel–Epstein system with a general reaction term. It is concerned with the global dynamics and asymptotic stability of the solutions. Sufficient conditions for the stability of the system's unique steady state solution are derived and confirmed through numerical analysis in Matlab.